Iron⁃calcium⁃biochar enhanced sludge deep dewatering and sludge⁃based biochar preparation - JIAO Hongming; FU Liang*; ZHOU Yingying; WANG Xurong; ZHANG Leilei; Gao Yonglin; ZHOU Dandan (能源环境保护)
Sludge dewatering is a crucial step in sludge disposal and resource recovery. While FeCl3 is commonly used to enhance sludge dewatering, it is ineffective for some residual sludges, resulting in a high moisture content in the sludge cake that fails to meet subsequent disposal requirements. In this study, we explored the synergistic effect of FeCl3, CaO, and biochar on the difficult dewatering residual sludge and its resource utilization. Under the optimal sludge dewatering with FeCl3 addition, CaO and biochar supplements could further enhance dewatering efficiency. When FeCl3 addition alone was used for the difficult-to-dewater residual sludge, the moisture content in the sludge cake was still as high as 60% ~70% under optimal conditions (FeCl3 9%). However, at this FeCl3 optimal conditions, CaO (2%) and rice husk biochar (2%) were added and then pressure filtrated for 7 minutes, the moisture content of the sludge cake could reduce to 44.08%, meeting the disposal requirements. Furthermore, the pH of the filtrate remained close to neutral, thus avoiding additional burden on the filtrate treatment process. The dehydrated sludge cake containing Fe and Ca elements were utilized to produce high-performance sludge-based biochar under 400 ℃. This biochar have large surface area and pore volume, and the surfaces rich in oxygen-containing functional groups. Notably, it showed remarkable efficiency in removing Cr6+, with an impressive adsorption capacity of 26.51 mg / g. This study has developed a comprehensive technical strategy to enhance the deep dewatering of difficult dewatering residual sludge and prepare high-performance sludge biochar, providing a valuable scientific basis and technical reference for the treatment and resource utilization of difficult dewatering residual sludge.